2017
DOI: 10.12659/msm.899368
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Esterase as a Biomarker in the Diagnosis of Periprosthetic Joint Infection

Abstract: BackgroundTotal joint arthroplasty (TJA) has been one of the most rewarding interventions for treating patients suffering from joint disorders. However, periprosthetic joint infection (PJI) is a serious complication that frequently accompanies TJA. Our study aimed to investigate the application of the leukocyte esterase (LE) strip in the diagnosis of PJI.Material/MethodsFrom October 2014 to July 2015, 72 patients who had undergone joint puncture after arthroplasty in our hospital were enrolled in this trial. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The original report on the utility of LE by Parvizi et al [6] found that a (þþ) LE cutoff provided 80.6% sensitivity in diagnosing PJI. Although there are a few centers reporting a higher sensitivity for the urinary LE test strip [10,11], most centers have reported lower values, including sensitivities of 69% [5], 66% [9], 81% [1], 84.21% [2], 75% [3], and 84% [4]. A recent large retrospective study of tests for PJI including the erythrocyte sedimentation rate, C-reactive protein, WBC count, polymorphonuclear neutrophil percentage, and LE found that LE had the lowest sensitivity of all tests [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original report on the utility of LE by Parvizi et al [6] found that a (þþ) LE cutoff provided 80.6% sensitivity in diagnosing PJI. Although there are a few centers reporting a higher sensitivity for the urinary LE test strip [10,11], most centers have reported lower values, including sensitivities of 69% [5], 66% [9], 81% [1], 84.21% [2], 75% [3], and 84% [4]. A recent large retrospective study of tests for PJI including the erythrocyte sedimentation rate, C-reactive protein, WBC count, polymorphonuclear neutrophil percentage, and LE found that LE had the lowest sensitivity of all tests [3].…”
Section: Discussionmentioning
confidence: 99%
“…Despite demonstrating urinary LE test strip sensitivities ranging from 69%-84%, previous studies [1,2,6,9] have suggested enthusiasm regarding the utility of the test strip for diagnosing PJI. In fact, one study demonstrating a test strip sensitivity of 81% suggested that a negative urinary LE test strip result may rule-out PJI with no need for further testing [1].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, seventeen studies involving a total of 1963 patients (571 joints with PJI) explored the diagnostic accuracy of leukocyte esterase for PJI [ 14 , 16 , 21 , 22 , 26 , 28 , 31 , 32 , 36 , 39 , 40 , 42 44 , 47 , 50 , 51 ]. All studies used the standard chemical test strip, among which two studies [ 16 , 32 ] used an automated reader to define the final result while thirteen studies [ 14 , 21 , 22 , 26 , 28 , 31 , 36 , 39 , 40 , 42 44 , 47 , 50 , 51 ] used the naked eye. The mean ages of included patients ranged from 60.3 to 71.0 years, and the proportion of males ranged from 21.7% to 60.9%.…”
Section: Resultsmentioning
confidence: 99%
“…When sampling tissue, 3 to 4 tissue samples should be obtained when treating PJI to facilitate organism identification and antimicrobial management, in the experience of 2 institutions 42,43 . Markers for PJI that were studied include presepsin 44 , adenosine deaminase 45 , procalcitonin 46,47 , interleukin-6 (IL-6) 48 , leukocyte esterase [49][50][51][52] , alpha-defensin [53][54][55] , D-dimer 56 , receptor activator of nuclear factor-kB ligand (RANKL), and osteoprotegerin 57 . Centrifugation of synovial fluid samples at 2,000 · gravity for 15 minutes improves leukocyte esterase testing, but testing should be performed on the top 2 mm of the centrifuged sample 58 .…”
Section: Diagnosismentioning
confidence: 99%